Cloud Native Infrastructure with Azure - Singh, Nishant; Kehoe, Michael (O'Reilly Media, Inc., 2022)
The cloud is becoming the de facto home for companies ranging from enterprises to startups. Moving to the cloud means moving your applications from monolith to microservices. But once you do, maintaining and running these services brings its own level of complexity. The answer? Modularity, deployability, observability, and self-healing capacity through cloud native development. With this practical book, Nishant Singh and Michael Kehoe show you how to build a true cloud native infrastructure on Microsoft Azure, following guidelines from the Cloud Native Computing Foundation (CNCF). DevOps and site reliability engineers will learn how adapting applications to cloud native early in the design phase helps you fully utilize the elasticity and distributed nature of the cloud. Chapters include: "Introduction: Why Cloud Native?" "Infrastructure as Code: Setting Up the Gateway" "Containerizing Your Application: More Than Boxes" "Kubernetes: The Grand Orchestrator" "Creating a Kubernetes Cluster on Azure" "Observability: Following the Breadcrumbs" "Service Discovery and Service Mesh: Finding New Territories and Crossing Borders" "Networking and Policy Management: Behold the Gatekeepers" "Distributed Databases and Storage: The Central Bank" "Getting the Message" "Serverless"